Does tea consumption during early pregnancy have an adverse effect on birth outcomes?. Issue 3 (21st March 2017) - Lu, Jin‐Hua; He, Jian‐Rong; Shen, Song‐Ying; Wei, Xue‐Ling; Chen, Nian‐Nian; Yuan, Ming‐Yang; Qiu, Lan; Li, Wei‐Dong; Chen, Qiao‐Zhu; Hu, Cui‐Yue; Xia, Hui‐Min; Bartington, Suzanne; et al.
Abstract: Background: Tea, a common beverage, has been suggested to exhibit a number of health benefits. However, one of its active ingredients, caffeine, has been associated with preterm birth and low birthweight. We investigated whether tea consumption during early pregnancy is associated with an increased risk of preterm birth and abnormal fetal growth. Methods: A total of 8775 pregnant women were included from the Born in Guangzhou Cohort Study. Tea consumption (type, frequency, and strength) during their first trimester and social and demographic factors were obtained by way of questionnaires administered during pregnancy. Information on birth outcomes and complications during pregnancy was obtained from hospital medical records. Results: Overall habitual tea drinking (≥1 serving/week) prevalence among pregnant women was low, at 16%. After adjustment for potential confounding factors (eg, maternal age, educational level, monthly income) tea drinking during early pregnancy was not associated with an increased risk of preterm birth or abnormal fetal growth (small or large for gestational age) ( P >.05). Conclusions: We did not identify a consistent association between frequency of tea consumption or tea strength and adverse birth outcomes among Chinese pregnant women with low tea consumption. Our findings suggest that occasional tea drinking during pregnancy is not associated with increased risk of preterm birth or abnormal fetal growth. Given the high overall number of annual births in China, our findings have important public health significance.